CSR as hypocrisy avoidance: a conceptual framework. Issue 1 (18th February 2019) - Jauernig, Johanna; Valentinov, Vladislav
Abstract : Purpose: The theoretical understanding of CSR is caught on the horns of the dilemma between the ethical and instrumental approaches. The strategic turn in CSR has brought the dilemma to a new head. The purpose of this paper is to develop a novel argumentative strategy to address the dilemma. Design/methodology/approach: The paper weaves together the insights from the literatures on sociological institutionalism, organization theory, business ethics and institutional economics to elaborate the distinction between CSR communication and CSR action that is actually undertaken and visible to stakeholders. This distinction is at the core of the "hypocrisy avoidance" approach which puts the above dilemma in a new light. Findings: According to the "hypocrisy avoidance" approach, the CSR communication constitutes a competitive arena where corporations are looking for reputational gains. Competitive pressures give rise to an inflationary dynamics of the CSR communication which consequently runs up against credibility problems. These problems are addressed by the real CSR policies which legitimate the corporate employment of the CSR communication as an instrument of competition. Practical implications: The theoretical dilemma between the ethical and instrumental approaches manifests itself in the justification of skepticism toward CSR communication. This skepticism, which may be to the detriment of a corporation's license to operate, may turn out to be a driving force of CSR action. Social implications: Despite the charges of corporate hypocrisy, CSR communication may play a role in the alleviation of business-society tensions. This role is however subject to two limitations. First, if CSR communication is used as instrument of competition, it is unlikely to translate into CSR action perfectly. Second, corporations would likely prioritize more visible CSR actions over less visible ones. Originality/value: The novel implication of the "hypocrisy avoidance" approach is that CSR actions present credible commitments or "hostages" enabling the productive interaction between corporations and their stakeholders. This implication integrates some of the components of the ethical and instrumental approaches, while drawing inspiration from the institutional economics and institutional ethics literatures.